Test-retest reliability of selected ground reaction force parameters and their symmetry during running - Bennell, K.; Crossley, K.; Wrigley, T.; Nitschke, J. (Journal of Applied Biomechanics, 1999)
The aim of our study was to assess the interday test-retest reliability (focussing on the separate contribution of systematic and random error) of selected 10-trial mean ground reaction force (GRF) parameters and GRF symmetry indices measured during running. Ten competitive male heel-strike runners (aged, 26.2 ± 5.7 years) performed 10 successful running trials across the force platform at a constant velocity of 4.0 m · s-1 ±10% wearing their customary running footwear. The testing procedure was repeated under similar conditions 1 week later. The results showed no statistically significant differences between the means of Test 1 and Test 2 for most GRF parameters and symmetry indices, indicating non-significant systematic error. Correlation coefficients ranged from 0.73 to 0.99 for GRF parameters. Random error was small with SEmeas less than 10% of the Test 1 mean value for almost all GRF parameters. Symmetry indices displayed correlation coefficients ranging from -0.44 to 0.91. Based on these and the size of the SEmeas, the symmetry indices displayed variable reliability, with the most reliable being those associated with peak vertical active force and peak horizontal propulsive force.